PENERAPAN STRATEGI THINK TALK WRITE (TTW) DALAM PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 009 TEMBILAHAN - Azrah, Meri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
This research was motivated by the low results of third-grade students learn math SD Negeri 009 Tembilahan, as seen from the mastery learning students, from 31 students only 11 students (35.48%), which reached the specified KKM is 70. To be improved learning through research by applying a talk think write strategy (TTW). The purpose of this research is to improve mathematics learning outcomes by implementing the strategy talk think write strategy (TTW). This research is a class act who performed at SD Negeri 009 Tembilahan with third grade students study subjects with the number of students 31 students. This study was conducted in two cycles, each consisting of two meetings and one daily tests. Research carried out through four stages: stats phase, the implementation phase, the stage of observation and reflection stages. The data used in this study focuses on improving learning outcomes. Data collection techniques used in this research is the engineering test, and analysis techniques used are descriptive analysis. The study states that the results of students' mathematics learning has increased after applied talk think write strategy (TTW). This is evidenced by the thoroughness and the acquisition of mathematics learning outcomes of students has increased. On the preliminary data the number of students reaching the KKM is 13 students (41.94%) with an average of 61.55 learning outcomes. In the first cycle increased with the number of students who completed or reached KKM total of 20 students (64.52%) with average learning results obtained at 68.71. And the second cycle mastery increased by 28 students (90.32%) with the average achieved learning outcomes at 79.68.